Influence of Azolla filiculoides on Dairy Cow Milk Production and Improvements in Macro Nutrients and Milk Quality Indicators (International Journal of Scientific Research in Science and Technology, 2026)
The dairy industry in India plays a pivotal role in rural development, employment, and nutritional security, making the quality of milk produced a key factor for both consumer health and economic viability. Enhancing milk quality, particularly in terms of fat, protein, and casein content, is essential for the production of high-value dairy products. Azolla filiculoides, a nutrient-rich and sustainable feed supplement, has shown potential to significantly improve these milk quality parameters. In a study involving 20 lactating HF crossbreed cows, Azolla supplementation led to notable increases in milk yield, with improvements ranging from 13.70% to 30.89%. Milk fat content ranged from 2.49% to 4.98%, protein content increased from 2.63%-3.24% to 3.16%-3.98%, and casein levels improved from 2.01%-2.3% to 2.66%-3.04%. Minimal changes were observed in lactose and galactose levels, indicating that while Azolla enhances fat and protein content, it does not significantly alter milk sugars. These results highlight A. filiculoidesas an effective, sustainable feed supplement that enhances milk quality, supporting the dairy industry’s objectives of improving nutritional outcomes and economic sustainability.